Epidemiology and outcomes of hyponatremia in patients with COVID-19—A territory-wide study in Hong Kong - Chan, Gordon Chun Kau; Wong, Chun Ka; So, Benjamin Y. F.; Ng, Jack Kit Chung; Lui, Grace Chung Yan; Szeto, Cheuk Chun; Hung, Ivan Fan Ngai; Tse, Hung Fat; Tang, Sydney C. W.; Chan, Tak Mao; Chow, Kai Ming; Yap, Desmond Y. H. (Frontiers in Medicine, 2023)
Background: Hyponatremia is common in COVID-19, but its epidemiology and impact on clinical outcomes in relation to different variants, especially the Omicron variant, requires further clarification. Methods: This was a territory-wide retrospective study to investigate the epidemiology and outcomes of COVID-19 patients with hyponatremia from 1 January 2020 to 31 March 2022 in Hong Kong. The primary outcome was 30-day mortality of patients with COVID-19 and hyponatremia at presentation. Secondary outcomes included rate of hospitalization, intensive care unit (ICU) hospitalization, overall duration of hospitalization and duration of ICU hospitalization. Results: A total of 53,415 COVID-19 patients were included for analysis, of which 14,545 (27.2%) had hyponatremia at presentation. 9813 (67.5%), 2821 (19.4%) and 1911 (13.1%) had mild (130 to <135 mmol/L), moderate (125 to <130 mmol/L) and severe hyponatremia (<125 mmol/L) at presentation respectively. Age, male sex, diabetes, active malignancy, white cell count, serum creatinine, hypoalbuminemia, C-reactive protein and viral loads were independent predictors for hyponatremia in COVID-19 patients (P<0.001, for all). Hyponatremic patients had increased 30-day mortality (9.7% vs. 5.7%, P<0.001), prolonged hospitalization (11.9 ± 15.1 days vs. 11.5 ± 12.1 days, P<0.001), and more ICU admissions (7.0% vs. 3.3%, P<0.001). Patients diagnosed during the “fifth wave” Omicron BA.2 outbreak had 2.29-fold risk (95% CI 2.02-2.59, P<0.001) of presenting with hyponatremia compared to other waves. Conclusions: Hyponatremia is common among COVID-19 patients, and may serve as a prognostic indicator for unfavorable outcomes and increased healthcare utilization in the evolving COVID-19 outbreak.